Quality of Life of Caregivers of Psychiatric Patients: A Case Study of Hope and Beyond Treatment Centre Lubaga Division - Patricia Bennitah Nabuuma (Uganda Christian University, 2024)
This study investigated the quality of life of care givers of psychiatric patients at Hope and Beyond treatment centre in Rubaga division. The research aimed to understand the challenges faced by caregivers and the factors influencing their wellbeing. A mixed- methods approach was employed, utilizing both qualitative and quantitative data collection methods, including interviews. The findings revealed that 40% of care givers reported a good quality of life, while 46.67% indicated poor to very poor quality of life, primarily due to prolonged care giving durations and inadequate access to mental health services. The study concluded that enhancing support systems and resources for care givers is essential to improve their quality of life. These findings underscore the need for targeted interventions to address the unique challenges faced by care givers, ultimately contributing to better health outcomes for both care givers and patients.